2020
DOI: 10.30520/tjsosci.748404
|View full text |Cite
|
Sign up to set email alerts
|

Üni̇versi̇te Öğrenci̇leri̇nde Covid-19 Korkusu Ve Beli̇rsi̇zli̇ğe Tahammülsüzlük

Abstract: COVID-19 olarak bilinen koronavirüs Çin ve diğer birçok ülkeye çok hızlı bir şekilde yayılarak akut bulaşıcı bir salgınına neden olmuştur. Bu salgın kısa sürede ülkemize de ulaşmıştır. Virüsün yayılmasını önlemek için pek çok tedbir alınmış, insanların gündelik yaşamları ani ve beklenmedik şekilde değişime uğramıştır. Tedbirler kapsamında, üniversiteler kapatılarak uzaktan eğitim sistemine geçilmiştir. Bu değişim, üniversite öğrencilerini pandemiden en çok etkilenen gruplardan biri haline getirmiştir. Bu neden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
34

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 21 publications
2
24
0
34
Order By: Relevance
“…In addition, the physical symptoms or as it is called the manifestations of panic if they appear, might come accidentally for any disorder related to the meaning of worry or fear (Becker, et, al., 2007). The results of this study is in consistent with the study (Duman, 2020;Gristenko, et, al., 2020;Lee & You, 2019). But it differs from the study (Wang & Zhao, 2020) about the level of the fear of COVID-19 among the universities students.…”
Section: Questionsupporting
confidence: 93%
“…In addition, the physical symptoms or as it is called the manifestations of panic if they appear, might come accidentally for any disorder related to the meaning of worry or fear (Becker, et, al., 2007). The results of this study is in consistent with the study (Duman, 2020;Gristenko, et, al., 2020;Lee & You, 2019). But it differs from the study (Wang & Zhao, 2020) about the level of the fear of COVID-19 among the universities students.…”
Section: Questionsupporting
confidence: 93%
“…It has been stated that fear of COVID-19 and other negative psychological effects were greater in the beginning of the pandemic, and women and younger individuals were more affected by them, and these effects have decreased in later periods [62,63]. Research results revealing that fear during the COVID-19 outbreak are similar between genders show that its effects on people living in different countries or geographies may differ depending on the course of the pandemic [24,62,64].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic causes widespread anxiety, worry and fear in people. Despite the availability of different vaccines, the mutation of the virus and the emergence of different variants of the virus causes these negative psychological effects to continue [20,24,25].…”
mentioning
confidence: 99%
“…When individuals have a high intolerance to uncertainty; It can be observed that individuals tend to perceive uncertain situations as unpleasant and stressful situations, avoid uncertainty, and experience disruption in their functionality in situations involving uncertainty (Buhr & Dugas, 2002). As a result of the research conducted by Duman (2020) on university students, it was observed that the participant group had a moderate intolerance to uncertainty. As a result of their research on university students, Gecgin and Sahranc (2017) found that women have higher levels of intolerance to uncertainty than men.…”
Section: Discussionmentioning
confidence: 99%